The veridical Near-Death Experience Scale: construction and a first validation with human and artificial raters - Greyson, Bruce; Long, Jeffrey; Holden, Janice Miner; Jourdan, Jean-Pierre; King, Robert A.; Mays, Suzanne; Mays, Robert; Rivas, Titus; Tassell-Matamua, Natasha; van Lommel, Pim; Woollacott, Marjorie; Tressoldi, Patrizio (Frontiers in Psychology, 2025)
IntroductionIn this study, we describe the construction of the veridical Near-Death Experience Scale (vNDE Scale), a structured instrument for evaluating the evidential strength of perceptions reported during near-death experiences (NDEs), and its first validation by human and artificial raters.MethodsThe construction was implemented using a typical Delphi Method. The first draft of the scale was evaluated by 13 experts in NDE, who were asked to suggest revisions and comments within a month for the first round and 20 days for the second round.ResultsA general consensus was achieved on the second round on eight criteria related to the timing of the investigation, the medical and physical conditions, the level of third-person verification, and the number, type, and quality of perceptions reported by the near-death experiencer, to be rated on a four-level Likert scale. The validation phase consisted of the application of the vNDE Scale to 17 cases of potentially veridical NDEs by 11 independent human raters and three artificial raters based on Large-Language Models. In 14 of the17 cases (82.3%), the overall agreement between human and artificial judges was over 75%, considering the two close levels of evidence strength, i.e., moderate plus strong, low plus very low, or vice-versa.DiscussionThe vNDE Scale is a practical tool for evaluating the evidential strength of perceptions reported by near-death experiencers.